1999
DOI: 10.3141/1694-06
|View full text |Cite
|
Sign up to set email alerts
|

User Requirements and Willingness To Pay for Traffic Information Systems: Case Study of Sydney, Australia

Abstract: The field of information provision to motorists has seen remarkable technological innovations in recent years. These techniques are generally classified under advanced traveler information systems (ATISs). These systems are designed to bring travel time savings and congestion alleviation to commuters. In the context of determining who will use this information system, what types of information are required, and how traffic information affects traveler behavior, the user needs and preferences derived from a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Surveys show that drivers like the idea of VMSs, whether they use them or not, and seem to want to be able to find such systems useful in their particular circumstances. Most drivers make routing choices while under way (as opposed to before their trips), and drivers want to minimize the time spent in congestion (2).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys show that drivers like the idea of VMSs, whether they use them or not, and seem to want to be able to find such systems useful in their particular circumstances. Most drivers make routing choices while under way (as opposed to before their trips), and drivers want to minimize the time spent in congestion (2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The radio is the most popular source of traffic information, perhaps because it is available to most drivers from an in-car radio; however, dedicated radio-based ATISs are infrequently used in Milwaukeemostly to control parking during special events. A study conducted in Australia found that only 37% of respondents were satisfied (2). Arterial VMSs can be as efficient as the radio from the point of view of providing information where it is needed, with the potential for continuous updating.…”
Section: Sources Of Traffic Informationmentioning
confidence: 99%
“…The ATGIS should provide the necessary information based upon end users' information preferences and present them in a perceivable format (visual display, metrics, and so on) for them to have an influence on travel behavior [18]. In a case study conducted in Sydney, Australia, the users listed accident information as their major information requirement, followed by traffic conditions and alternative route information [19]. Another study conducted in 48 US states showed that the users value road and traffic information as the most important feature of travel information systems [20].…”
Section: System Design Preferencesmentioning
confidence: 99%
“…In general, results indicate that consumers are willing to pay only modest sums, no matter what content the ATIS provides. Although many studies have presented both choices to the respondents, the literature results are consistent: users prefer a per-call fee to a monthly flat rate (3)(4)(5). Table 1 is a summary of the literature reviewed.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Khattak et al used a panel-type data set to find that TravInfo users in the Bay Area would call frequently for $0.25 if service were customized to their needs, but the number of calls would decline at higher prices (5). Similarly, Kim and Vandebona estimated that only 33 percent of Sydney, Australia, residents would pay US$0.25 for information (4).…”
Section: Literature Reviewmentioning
confidence: 99%